Penetration depth and enamel hardness effects of resin infiltrate and fissure sealant in MIH-affected molars: An in-vitro comparison - Tseveenjav, Battsetseg; Mulic, Aida; Waltimo-Sirén, Janna; Tulek, Amela (Springer Nature, 2026)
Purpose
To measure and compare the penetration depth of two treatment materials, a resin infiltrate (RI) and a fissure sealant (FS), into the enamel of MIH-affected molars without post-eruptive breakdown, and the materials’ effect on the hardness of the hypomineralised enamel.
Methods
Two groups of sixteen mildly affected MIH-molar specimens were treated with either RI or FS. Two additional groups of untreated MIH specimens and healthy specimens served as a positive and a negative control, respectively. Specimens were treated and thereafter analysed using scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (SEM–EDX), and hardness testing machine. Penetration depth of treatment material, surface element analysis and hardness values were measured.
Results
There was a statistically significant difference in penetration depth between the tested materials (p < 0.05). RI penetrated deeper and more evenly into the affected enamel of MIH-lesions, compared to FS. EDX analysis showed statistically significant differences in mineral contents between the study groups (p < 0.05), and presence of fluoride was detected only in the FS group. In the RI-treated enamel, the hardness reached values twice as high as compared to that in the untreated MIH-group but remained below the hardness of healthy enamel. Mean hardness values in FS samples were not significantly different from those of untreated MIH-samples (p ˃ 0.05).
Conclusion
The low-viscosity RI penetrated more deeply into porous hypomineralised enamel of MIH-affected molars compared to the FS. RI increased enamel hardness and altered mineral content. These findings encourage clinical use of RI as minimally invasive treatment of mildly MIH-affected molars to prevent post-eruptive breakdown.